2020
DOI: 10.1002/jcsm.12618
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of cachexia in the human fibrosarcoma HT‐1080 mouse tumour model

Abstract: Background Cancer cachexia is a complex metabolic disease with unmet medical need. Although many rodent models are available, none are identical to the human disease. Therefore, the development of new preclinical models that simulate some of the physiological, biochemical, and clinical characteristics of the human disease is valuable. The HT-1080 human fibrosarcoma tumour cell line was reported to induce cachexia in mice. Therefore, the purpose of this work was to determine how well the HT-1080 tumour model co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 43 publications
(96 reference statements)
2
15
0
Order By: Relevance
“…Even when ectopic injections are used, variability can occur depending on the site 143 , 144 , affecting the pathophysiology and/or time frame of cachexia development, which also effects the rate of tumour metastasis 144 . Human-derived tumours implanted in immune-deficient mice have also been used to allow a better representation of human cancer cachexia and its response to therapeutic agents 145 ; however, these models have a major caveat of lacking proper antitumour immune responses. Genetically engineered mouse models attempt to produce naturally occurring tumours with mutational signatures similar to those seen in human cancer 146 148 .…”
Section: Cytokines and Cachexiamentioning
confidence: 99%
“…Even when ectopic injections are used, variability can occur depending on the site 143 , 144 , affecting the pathophysiology and/or time frame of cachexia development, which also effects the rate of tumour metastasis 144 . Human-derived tumours implanted in immune-deficient mice have also been used to allow a better representation of human cancer cachexia and its response to therapeutic agents 145 ; however, these models have a major caveat of lacking proper antitumour immune responses. Genetically engineered mouse models attempt to produce naturally occurring tumours with mutational signatures similar to those seen in human cancer 146 148 .…”
Section: Cytokines and Cachexiamentioning
confidence: 99%
“…As a critical upstream of protein turnover alteration, inflammation plays a key role in the development of muscle wasting in cancer patients. Indeed, either released by the tumor or immune cells, pro-inflammatory cytokines like TNF-α, TWEAK, IL-6, IL-1β, IL-8, and INFγ have been found to be upregulated at a systemic level in animals ( Costelli et al, 1993 ; Baltgalvis et al, 2008 ; Zhou et al, 2010 ; Toledo et al, 2016 ; Guo et al, 2017 ; Chen T. et al, 2018 ; Bae et al, 2020 ; Bernardo et al, 2020 ; Huot et al, 2020 ) and in cancer patients ( Scott et al, 1996 ; DeJong et al, 2005 ; Moses et al, 2009 ; Skipworth et al, 2011 ; Op den Kamp et al, 2013 ; Puig-Vilanova et al, 2015 ; Johns et al, 2017 ; Riccardi et al, 2020 ). Importantly, from a study that included 661 breast cancer patients, systemic inflammatory cytokines were associated with a poor survival, reduced disease-specific survival and disease-free survival ( Cho et al, 2018 ).…”
Section: Potential Other Cellular Mechanisms Of Muscle Deconditioning In Breast Cancer Patients: What Can We Learn From Other Cancers?mentioning
confidence: 99%
“…MSTN and/or its downstream targets have been found to be upregulated in many experiments on cancer cachexia ( Costelli et al, 2008 ; Bonetto et al, 2009 ; Zhou et al, 2010 ; Murphy et al, 2011 ; Aversa et al, 2012 ; Padrão et al, 2013 ; Chacon-Cabrera et al, 2014 ; Silva et al, 2015 ; Chen M. C. et al, 2016 ; Sun et al, 2016 ; Chen M. C. et al, 2018 ; Salazar-Degracia et al, 2018 ; Lee et al, 2019 ; Huot et al, 2020 ), as well as in studies exploring the effect of doxorubicin administration ( Kavazis et al, 2014 ; Liu et al, 2019 ). Acting through the same receptor than MSTN (ActRIIB), Activin A is also found to be increased in cancer cachexia ( Leto et al, 2006 ; Loumaye et al, 2015 ; Matsuyama et al, 2015 ; Chen J. L. et al, 2016 ; Chen M. C. et al, 2016 ; Barreto et al, 2017 ; Zhong et al, 2019 ; Bernardo et al, 2020 ) and an independent prognosis factor of survival in cancer patients ( Loumaye et al, 2017 ). Several authors conducted experiments with inhibition of the MSTN/Activin A pathway and found a reduction, or even a complete reversal, in the decrease of muscle mass and function in pre-clinical models ( Liu et al, 2008 ; Benny Klimek et al, 2010 ; Murphy et al, 2011 ; Busquets et al, 2012a , b ; Gallot et al, 2014 ; Hatakeyama et al, 2016 ; Levolger et al, 2019 ; Ojima et al, 2020 ; Pettersen et al, 2020 ), leading to the consideration of this pharmacological strategy for human cancer patients.…”
Section: Potential Other Cellular Mechanisms Of Muscle Deconditioning In Breast Cancer Patients: What Can We Learn From Other Cancers?mentioning
confidence: 99%
“…In this simplified model, REE encompasses the basal metabolic rate and the contribution of adaptive thermogenesis determined by changes in temperature and diet. It seems obvious that animals with cancer would have increased REE given the presence of highly metabolic tumor cells, however, the data supporting this assumption are mixed 6 .…”
Section: Introductionmentioning
confidence: 99%